2014
DOI: 10.1177/0265407514525888
|View full text |Cite|
|
Sign up to set email alerts
|

Above and below baselines

Abstract: The current study tests an explanation inspired by social baseline theory (Beckes & Coan, 2011. Social baseline theory: The role of social proximity in emotion and economy of action. Social and Personality Psychology Compass, 5, 976-988. doi:10.1111Compass, 5, 976-988. doi:10. /j.1751Compass, 5, 976-988. doi:10. -9004.2011.00400) for the mixed blessings associated with received emotional support from one's partner. We reason that the receipt of emotional support engenders benefits only up to individualized bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…One study (Rafaeli et al, 2008) showed hindrance (bad) to trump support (good). Another study (Bar-Kalifa & Rafaeli, 2013) showed nonmonotonic effects for emotional support, with low-level support exerting stronger effects than high-level support.…”
Section: Discussionmentioning
confidence: 99%
“…One study (Rafaeli et al, 2008) showed hindrance (bad) to trump support (good). Another study (Bar-Kalifa & Rafaeli, 2013) showed nonmonotonic effects for emotional support, with low-level support exerting stronger effects than high-level support.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the evolutionary primacy of negative stimuli and their tendency to exert a stronger effect than positive stimuli across various domains, including relational ones. Indeed, daily relational negative behaviors tend to exert a stronger effect on partners’ mood than positive ones (e.g., Bar-Kalifa & Rafaeli, 2015; Rafaeli et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We define support as the amount of support (i.e., emotional support, instrumental/practical support, helping behaviors, responsiveness, or caregiving) that providers extend or intend to extend. Although receiving higher levels of support does not always produce favorable outcomes (e.g., Bolger & Amarel, 2007;Bolger et al, 2000;Gleason et al, 2003;Howland & Simpson, 2010), accumulating longitudinal and experimental evidence suggests that receiving support is beneficial when people want, need, or try to elicit support from a partner (Bar-Kalifa & Rafaeli, 2013Rafaeli, , 2015Crockett et al, 2017;Deelstra et al, 2003;Feinstein, 1988, as cited in Dunkel-Schetter et al, 1992Girme et al, 2013;Merluzzi et al, 2016;Siewert et al, 2011). For example, findings from daily diary studies indicate that receiving less support than one wants or needs is far more costly to an individual's wellbeing than is receiving too much support (Bar-Kalifa & Rafaeli, 2013Rafaeli, , 2015Siewert et al, 2011).…”
Section: Model Of Positive Expressivity's Effects On Support For Negamentioning
confidence: 99%
“…Although receiving higher levels of support does not always produce favorable outcomes (e.g., Bolger & Amarel, 2007;Bolger et al, 2000;Gleason et al, 2003;Howland & Simpson, 2010), accumulating longitudinal and experimental evidence suggests that receiving support is beneficial when people want, need, or try to elicit support from a partner (Bar-Kalifa & Rafaeli, 2013Rafaeli, , 2015Crockett et al, 2017;Deelstra et al, 2003;Feinstein, 1988, as cited in Dunkel-Schetter et al, 1992Girme et al, 2013;Merluzzi et al, 2016;Siewert et al, 2011). For example, findings from daily diary studies indicate that receiving less support than one wants or needs is far more costly to an individual's wellbeing than is receiving too much support (Bar-Kalifa & Rafaeli, 2013Rafaeli, , 2015Siewert et al, 2011). Seekers who receive more (vs. less) responsive support (according to coders) when discussing their personal problems experience more favorable changes immediately after the support interaction (e.g., increased positive affect, felt acceptance, and engagement in positive reframing; and decreased negative affect) and over time (e.g., increased engagement in constructive coping and self-efficacy), in part because of their accurate detection of the partner's responsive support (Lemay & Neal, 2014).…”
Section: Model Of Positive Expressivity's Effects On Support For Negamentioning
confidence: 99%